Unsynchronized nasal intermittent positive pressure versus nasal continuous positive airway pressure in preterm infants after extubation. (June 2014) - Kahramaner, Zelal; Erdemir, Aydin; Turkoglu, Ebru; Cosar, Hese; Sutcuoglu, Sumer; Ozer, Esra Arun
Abstract Objective: To determine the effect of unsynchronized nasal intermittent positive pressure ventilation compared to continuous positive airway pressure in preterm infants after extubation. Methods: A total of 67 premature infants who were <35 weeks gestation and/or <2000 g birth weight and received mechanical ventilation because of respiratory distress syndrome (RDS) were studied. Infants were randomized to receive either unsynchronized nasal intermittent positive pressure ventilation (NIPPV) with shortened endotracheal tube (Group 1) or nasal continuous positive airway pressure (NCPAP) with binasal prongs (Group 2) after extubation. Extubation failure and neonatal outcomes were recorded in each group. Results: There were no significant differences in clinical characteristics between the two groups. The prevalence of re-intubation and post-extubation atelectasis were higher in CPAP group (p = 0.03 and p = 0.01). No differences were observed in the prevalence of IVH, ROP, PDA, NEC, sepsis, pneumothorax, BPD and BPD/death between the groups while the mortality was higher in NCPAP group (p < 0.01). Neither procedure had any serious side effects such as intestinal perforation. Conclusion: NIPPV (although non-synchronized and delivered by single nasal prong) had a better effect than NCPAP after extubation of preterm infants on mechanical ventilation in respect to reducing the prevalence of post-extubation atelectasis, re-intubation and also death.